The Two Celamas of Luis Mateo Díez: Memory and Oblivion (Castilla. Estudios de Literatura, 2015)
The article explores the development of the narrative space in Luis Mateo Díez´s trilogy, El reino de Celama. With a critical and theoretical support, it explains the intrinsic relationship between space and its inhabitants, and states that there is an implicit differentiation between two Celamas that are separated by time, but still coexist in the same space. Each of these Celamas would correspond with two different values: memory (light), and oblivion (darkness).
Keywords: Luis Mateo Díaz; space; memory; oblivion